Accumulation of Cadmium and Lead in the muscles of Sardinella maderensis and Alosa fallax caught from the Syrian marine waters. - Alshikh Rasheed, Reem; Galiya , Mohammad; Almajid, Zouhair; Laika, Houssam (Latakia University Journal -Biological Sciences Series, 2023)
The research was conducted on Sardinella maderensis and Alosa fallax based on their importance for local consumption as food for humans and bait in catching other fish species. Fish samples were collected from the Ras Al-Baseet area north of the Syrian coast during the period between 10/20/2021 and 9/14/2022. 10g (wet weight) was taken from the muscles of 360 individuals. The concentrations of Cadmium and Lead were measured using an atomic absorption device (AAS) using flame technology at the Higher Institute of Marine Research Institute at Tishreen University. The results showed high values of Lead(0.11-1.54μg/g) and Cadmium (0.27-0.11μg/g) in Sardinella maderensis muscles as well as in the muscles of the Alosa fallax Lead(1.46, 1.02 μg/g) and Cadmium (0.26, 0.11 μg/g). g) in comparison with the cut-off values. Allowed by international organizations (FAO/WHO,2010),but they were within the permissible values. According to (FAO/WHO, 2003). for the two species caught in the marine waters of Lattakia Governorate - Syria. The highest values ​​were recorded for them in the summer of the study year 2021-2022 AD